1997
DOI: 10.1107/s0021889897002525
|View full text |Cite
|
Sign up to set email alerts
|

TheFdddfour-circle diffractometer for single-crystal X-ray studies at temperatures down to 9 K

Abstract: The Fddd four-circle diffractometer system has been developed to perform X-ray diffraction experiments at temperatures as low as 9 K. The diffractometer consists of: (i) a Siemens rotatinganode generator; (ii) a Huber goniometer with offset X circle; (iii) a Siemens Fast Scintillation Detector; and (iv) an APD '202' Displex cryogenic refrigerator. The belt-driven rotating anode gives an X-ray flux that is far in excess of that obtained from a sealed X-ray tube and leads to faster data collections and the oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…X‐ray crystallography : Single‐crystal X‐ray diffraction data were collected at 12 K on the Fddd diffractometer33 equipped with a Displex cryo‐refrigerator. Data were obtained up to 60° in 2 θ by using graphite monochromated Mo Kα radiation ( λ =0.71073 Å) from a needle‐shaped black single crystal (0.02×0.02×0.10 mm).…”
Section: Methodsmentioning
confidence: 99%
“…X‐ray crystallography : Single‐crystal X‐ray diffraction data were collected at 12 K on the Fddd diffractometer33 equipped with a Displex cryo‐refrigerator. Data were obtained up to 60° in 2 θ by using graphite monochromated Mo Kα radiation ( λ =0.71073 Å) from a needle‐shaped black single crystal (0.02×0.02×0.10 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Single crystals in the form of perfect tetrahedra with edges of up to 0.4 mm were grown by slow diffusion in a silicate gel. [22] X-ray diffraction studies: The relevant structure determination parameters are given in Table 1 [23] which consists of an APD 202 Displex cryogenic refrigerator on a Huber 512 goniometer with an offset c-circle, a Bruker Mo rotating anode generator (l 0.71073 ) and a fast scintillation detector. A dark red crystal was attached to a sharpened graphite rod (0.3 mm) by means of a lowtemperature epoxy glue and was mounted on the Displex.…”
Section: Methodsmentioning
confidence: 99%
“…(h) A redesigned sample mount. To enhance cooling times and equilibration of the measured temperature compared with that at the sample position, the sample mount has been modified from that used previously by Copley et al (1997). The principal change has been to reduce the volume of material being cooled between the diode, where the temperature measurement is carried out, and the sample position.…”
Section: System Overviewmentioning
confidence: 99%
“…All structural phase transitions were monitored, allowing an equilibration time of at least 10 min at each data point before the crystal centring was checked and data recorded. The crystals were all mounted as described by Copley et al (1997) on sharpened 0.5 mm graphite rods using a low-temperature epoxy resin (Oxford Instruments, TRZ0004). The calibration experiments showed that the temperature interpreted from the Lakeshore diode was accurate to within 0.5 K with a nominal stability of < 0.1 K.…”
Section: System Calibrationmentioning
confidence: 99%
See 1 more Smart Citation